2014
DOI: 10.1136/annrheumdis-2013-205124.174
|View full text |Cite
|
Sign up to set email alerts
|

A7.6 Neuropathic pain in rheumatic diseases: a cross-sectional study

Abstract: Introduction Pain is the most common symptom in rheumatic diseases. In its pathophysiology there is usually a disturbance in nociceptive perception by tissue damage, that evolve often to features of central pain, with characteristics of neuropathic pain (NP). Neuropathic pain in rheumatic diseases is a topic rarely addressed in the literature. Objectives Determine, in a cohort of patients with rheumatoid arthritis (RA), osteoarthritis (OA) axial (a-SpA) and peripheral (p-SpA) spondylarthritis, the prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
5
0
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 0 publications
2
5
0
3
Order By: Relevance
“…NP symptoms have only been sporadically tested in RA samples. The 17 % proportion of RA patients with likely NP found in this study was very similar to the 19 % prevalence reported by Meirinhos et al [ 21 ]. Conversely, Ahmed et al [ 20 ] reported that 28 % of RA patients had possible NP symptoms and 5 % were likely to be experiencing NP symptoms according to the painDETECT.…”
Section: Discussionsupporting
confidence: 91%
“…NP symptoms have only been sporadically tested in RA samples. The 17 % proportion of RA patients with likely NP found in this study was very similar to the 19 % prevalence reported by Meirinhos et al [ 21 ]. Conversely, Ahmed et al [ 20 ] reported that 28 % of RA patients had possible NP symptoms and 5 % were likely to be experiencing NP symptoms according to the painDETECT.…”
Section: Discussionsupporting
confidence: 91%
“…Полученные результаты согласуются с данными других авторов, согласно которым НБ при РА отмечается у 17-36% пациентов [8][9][10]. В работе S.M.W.…”
Section: общая характеристика больных ра (N=208)unclassified
“…Частота невропатических дескрипторов при РА варьирует в пределах 17-36% [8][9][10]. Что касается других ревматических заболеваний, то, например, при остеоартрите их частота составляет 30-66% [11][12][13][14], при анкилозирующем спондилите -13-33,5% [15,16].…”
unclassified
“…Pain is associated with consciousness and is a synonym of suffering; connected with motor organs, it is often caused by degenerative disease of joints [1], [2]. Progressive degenerations, at first of a cartilage and then of the following subcondral layers and finally of the bone tissue itself may be a symptom of ageing of an organism and wearing of the osteoarticular system [3], [4].…”
Section: Introductionmentioning
confidence: 99%